Hubungan Dukungan Sosial dengan Tingkat Stres pada Warga Binaan Pemasyarakatan Perempuan di Lembaga Pemasyarakatan - Akhmad Yanuar Fahmi (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2019)
Introduction: Social support is expected to reduce stress on inmates. Previous study stated that social support has no relationship with the level of stress on female prisoners while other study mentioned that social support has a significant effect on reducing stress levels on inmates. Based on these phenomena, the researchers were interested in examining the relationship of social support with stress levels in female prisoners, to find out implicitly the relationship between social support with stress levels.Method: This study used a cross-sectional technique. The number of samples was 59 female inmates in a prison in West Java with purposive sampling technique. Data collection in this study used survey employing the DASS questionnaire sheet and Social Provisions Scale. The statistical test used to process data is the Rank Spearman SPSS 22 test for windows 7. This research has been conducted by the Ethics Institute of Stikes Banyuwangi.Results: The results of the study found that most of the fostered residents received less social support as many as 34 respondents and 25 respondents experienced mild stress levels. The result of statistical calculation of Spearmen Rank obtained correlation co-efficient value of -0.665 and sig. (2-tailed) = 0.000 (<0.05), thus it means that there is a significant relationship between social support and the level of stress in female inmates.Conclusion: Female inmates who receive good social support will have a positive impact on their psychological i.e. not experiencing stress. Conversely, the less they get social support, the more they experience distress.